Detrimental Effect of Prolonged Lower Limb Static Stretching on Dynamic Balance in Older Adults with Knee Osteoarthritis: Lower Limb Static Stretching on Balance in Older Adults with Knee Osteoarthritis - Ghanbarpurshiadeh, Mohammad Reza; Chughtai, Muhammad Danial Baig; Uddin, Shahab; Liaquat, Maryam; Zaidi, Syeda Tanveer (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2025)
Due to the fast aging of the world's population, physiological alterations associated with age that impair postural control and boost the risk of falls are becoming more common. Falls are a major public health concern among the elderly, and knee osteoarthritis (OA). Objectives: To investigate the short-term effects of a multi-muscle lower limb stretching regimen on the balance performance of older adults with knee OA. Methods: Twenty-nine individuals with OA, aged 60 to 75 years, participated in a quasi-experimental study. Participants were divided into two groups: a control group (n=15) that performed placebo stretches and an intervention group (n=14) that underwent static stretching for five minutes each, targeting the hamstring, tensor fascia latae, and calf muscles. The Fullerton Advanced Balance (FAB) scale, the Timed Up and Go (TUG) test, the Functional Reach (FR) test, and knee range of motion (ROM) were used to assess mobility and balance outcomes both before and after the intervention. Results: Reduced FAB and FR scores and longer TUG times after stretching were indicative of a statistically significant loss in dynamic balance in the intervention group. The control population, on the other hand, showed no discernible changes in any of the balance metrics. The intervention group's knee range of motion improved somewhat, but this difference was not statistically significant. Conclusions: A single session of prolonged static stretching of lower limb muscles can acutely impair dynamic balance in older adults with knee OA. Immediate rest following such exercises is recommended to reduce the potential risk of falls in this vulnerable population.